1991
DOI: 10.1002/ar.1092300305
|View full text |Cite
|
Sign up to set email alerts
|

A method for preparing skeletal muscle fiber basal laminae

Abstract: Previous attempts to prepare skeletal muscle basal laminae (BL) for ultrastructural analyses have been hampered by difficulties in successfully removing skeletal muscle proteins and cellular debris from BL tubes. In the present study we describe a two phase method which results in an acellular muscle preparation, the BL of which are examined by light, transmission electron, and scanning electron microscopy. In the first phase, excised rat extensor digitorum longus muscles are subjected to x-radiation and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In particular, in the present paper, we compared different decellularization protocols. In the literature, the first decellularization protocol was developed by Carlson and Carlson [ 33 ], who proposed a method involving several steps: skeletal muscle was first treated with chelants and detergents (EDTA and Triton X-100), to disrupt and remove the cell membrane, then it was exposed to enzymatic digestion (DNase) and it was finally treated with sodium deoxycholate to remove cellular debris. Following decellularization, protocols were implemented and refined through the introduction of freezing/thawing cycles and further chemical (e.g., SDS) and enzymatic (e.g., trypsin, latrunculin B) reactions [ 14 , 15 , 16 , 17 , 18 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, in the present paper, we compared different decellularization protocols. In the literature, the first decellularization protocol was developed by Carlson and Carlson [ 33 ], who proposed a method involving several steps: skeletal muscle was first treated with chelants and detergents (EDTA and Triton X-100), to disrupt and remove the cell membrane, then it was exposed to enzymatic digestion (DNase) and it was finally treated with sodium deoxycholate to remove cellular debris. Following decellularization, protocols were implemented and refined through the introduction of freezing/thawing cycles and further chemical (e.g., SDS) and enzymatic (e.g., trypsin, latrunculin B) reactions [ 14 , 15 , 16 , 17 , 18 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The muscle retains the distal tendon attached to one extremity and conserves its morphology and stiffness, including intact arterial and venous basement membranes, in the absence of endogenous cells. The first method designed to obtain skeletal muscle decellularization dates back to the early 1990s [29]. That method, as well as more recent ones, are based on long, specific series of enzymatic and detergent treatments aimed at selectively eliminating any trace of cellular constituents, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Afterward the tissues were explanted and subjected sequentially to EDTA, Triton X-100, DNase and sodium deoxycholate to remove cells. Using this method they were able to obtain acellular muscle grafts [194]. Later studies reported decellularization methods that did not require the use of radiation or reimplanting the graft back into the donor.…”
Section: Skeletal Musclementioning
confidence: 99%